Efektifitas Pembangunan Sentra PKL Kuliner di Kota Surabaya - Agung Bayu Murti (Trunojoyo University of Madura, 2022)
Research on the analysis of the effectiveness of the PKL center development programneeds to be carried out, to analyze how the effectiveness of the PKL Center development for the government in urban planning and for the PKL itself in improving its performance as well as the socio-economic impact caused by the existence of the PKL center. Overall, the effectiveness of the central development of street vendors from the perspective of the government and community leaders shows that the central development of street vendors is very effective, especially in the context of law and order, restoring the function of roads and providing cheap and healthy food.